Pensioners' subjective economic well-being in European countries : comparisons behind the income satisfaction paradox - Palomäki, Liisa-Maria (fi=Turun yliopisto|en=University of Turku|, 2018)
The purpose of this doctoral thesis is to expand the relative perspective in the analysis of financial satisfaction in old age, by which is meant the formation of financial satisfaction as part of different types of comparisons. The old-age population is known to be financially more satisfied than other population groups, a paradoxical finding considering their generally lower-than-average income level. This phenomenon is called the satisfaction paradox. With the help of multilevel and longitudinal analyses, this study investigates how income levels in European countries and retirement are associated with subjective economic well-being. Questions of central importance to this study include to what degree satisfaction can be explained by the population group one compares oneself to, and to what degree one's current economic status is compared to one's own previous economic status. The results clarify our understanding of the relationship between objective income and subjective evaluations of economic well-being in the old-age population. The theoretical framework of this thesis consists of Nordic welfare research, quality of life research and economist-driven happiness research. The data consists of results from "The Welfare and Services survey in Finland" from the years 2004, 2006 and 2009 as well as a cross-section of and longitudinal data from EU-SILC (European Union Statistics on Income and Living Conditions) from the time period 2005−2013. Results show income and experience to be linked as presumed. Those with the highest income experienced their income as more adequate in making ends meet than did those with a lower income. This applies to Finnish pensioners as well as more broadly to older people living in Europe. Income growth also increased the sense of ease associated with income adequacy. However, results also showed that the oldest age groups experience a greater ease in making ends meet than might be assumed based on their income. For this reason, we cannot dismiss the existence of the satisfaction paradox. Retirement weakened the perception of income adequacy. However, the effect was not as dramatic as is generally thought. Perceptions of weakened adequacy cannot be explained by the absolute decrease in income, but rather by changes between a person's previous economic status and current status. A European comparison showed weakened perceptions of adequacy at retirement for those transferring directly from working life, but a significant improvement for the unemployed retiring and a slight improvement in the perceptions of those retiring from other statuses. These differences may, for instance, be linked to people's expectations on the sufficiency of their pension. For the unemployed and others, getting a pension means having a stable and continuous source of income. The Finnish study, on the other hand, showed that improved relative income status gained at retirement compared to the population at large increased the experience of income sufficiency. Experiences of income adequacy were weakened, however, when the individual's relative income status became higher in relation to that of other pensioners compared to previous status among active age population while still working. This may indicate that a newly retired person does not immediately consider other pensioners as his or her reference group, or it may be a general indication of weakened future prospects. Pensioners evaluate their income in relation to other pensioners rather than to the population as a whole, or to the population of active age. This applies to both younger and older old-age pensioners in different European countries. Income distribution within a country also does not have any bearing on pensioners' evaluation of income adequacy. What does matter, on the other hand, is the average income level of pensioners in the country, which can also be seen as an indication of the standard of living. In countries with a higher standard of living, pensioners perceived their income adequacy as lesser than in countries with a lower standard of living. This difference may be linked to the expectations on consumption created by different standards of living. All in all, it may be concluded that the financial satisfaction of the aged population is linked to income as well as to what we compare our own economic status. Retirement and the economic context of the country of residence play a role in these comparisons. Key terms: subjective economic well-being, perceived income adequacy, livelihood, retirement, financial satisfaction, reference group, EU-SILC

Tämän väitöskirjan tarkoitus on laajentaa ikääntyneiden taloudellisen tyytyväisyyden tutkimuksen suhteellista näkökulmaa, jolla tarkoitetaan taloudellisen tyytyväisyyden muodostumista osana erilaisia vertailuja. Ikääntyneiden tiedetään olevan muita väestöryhmiä tyytyväisempiä taloudelliseen tilanteeseensa, mikä on ristiriitainen havainto ottaen huomioon heidän keskimääräistä matalampi tulotasonsa. Ilmiötä on kutsuttu myös tyytyväisyysparadoksiksi. Tässä tutkimuksessa tarkastellaan monitaso- ja pitkittäisanalyysien avulla, millaisia yhteyksiä Euroopan maiden tulotasoilla ja eläkkeelle siirtymisellä on subjektiiviseen taloudelliseen hyvinvointiin. Keskeisiä kysymyksiä ovat missä määrin tyytyväisyys selittyy sillä, mihin väestöryhmään omaa taloudellista tilannetta verrataan ja missä määrin nykyistä tilannetta verrataan omaan aiempaan taloudelliseen tilanteeseen. Tulokset täsmentävät ymmärrystä objektiivisten tulojen ja subjektiivisten toimeentulokokemusten välisestä suhteesta ikääntyneiden väestöryhmässä. Tutkimuksen teoreettiset lähtökohdat ovat pohjoismaisessa hyvinvointitutkimuksessa, elämänlaaduntutkimuksessa ja taloustieteellisessä subjektiivisen hyvinvoinnin tutkimuksessa. Aineistoina on käytetty Suomalaisten Hyvinvointi ja Palvelut -kyselytutkimuksia vuosilta 2004, 2006 ja 2009 sekä Eurooppalaisen tulo- ja elinoloaineisto EU-SILC:n poikkileikkaus- ja pitkittäisaineistoja vuosilta 2005−2013. Tulokset osoittivat tulojen ja kokemusten olevan yhteydessä toisiinsa oletetulla tavalla. Suurituloisimmat kokivat tulojen riittävän paremmin menojen kattamiseen kuin pienituloiset. Tämä koski sekä suomalaisia eläkeläisiä että laajemmin Euroopassa asuvia ikääntyneitä. Tulojen kasvu myös lisäsi koetun toimeentulon helppoutta. Tulokset kuitenkin osoittivat, että vanhimmat ikäryhmät kokevat toimeentulonsa helpommaksi kuin tulojen perusteella voisi olettaa. Tämän vuoksi tyytyväisyysparadoksin olemassaoloa ei voida kumota. Eläkkeelle siirtyminen heikensi koettua toimeentuloa jonkin verran. Vaikutus ei kuitenkaan ole yhtä jyrkkä kuin yleisesti arvellaan. Heikentyneet toimeentulokokemukset eivät selity absoluuttisella tulojen vähenemisellä, vaan pikemminkin aiemman taloudellisen aseman ja nykytilanteen välisillä muutoksilla. Eurooppalainen vertailu osoitti työstä eläkkeelle siirtyneiden toimeentulokokemusten heikkenevän mutta työttömyydestä eläköityvien paranevan selkeästi ja muista asemista eläköityvien paranevan hieman. Erot voivat liittyä esimerkiksi siihen, millaisia odotuksia eläkkeiden riittävyydelle asetetaan. Työttömien ja muiden kohdalla eläketulo lisää myös varmuutta toimeentulon jatkuvuudesta. Suomalainen vertailu puolestaan osoitti, että eläkkeelle siirtymisen myötä kohentunut tuloasema väestön keskuudessa lisää kokemusta toimeentulon riittävyydestä. Kokemuksia sen sijaan heikensi tilanne, jossa uusi tuloasema eläkeläisten keskuudessa oli parempi kuin aiemmin työikäisten keskuudessa. Tämä voi kertoa siitä, että muita eläkeläisiä ei pidetä vertailuryhmänä heti eläkkeelle siirtymisen jälkeen tai yleisemmin heikentyneistä tulevaisuudennäkymistä. Koko väestön tai työikäisten sijaan eläkkeellä olevat arvioivat toimeentuloaan suhteessa toisiin eläkeläisiin. Tämä koskee sekä nuorempia että ikääntyneempiä vanhuuseläkeläisiä eri Euroopan maissa. Maiden sisäisellä tulonjaolla ei ole merkitystä eläkeläisten toimeentulokokemusten kannalta. Sen sijaan maiden keskimääräisellä eläkeläisten tulotasolla, jonka voidaan katsoa kuvaavan myös maiden elintasoa, on merkitystä. Korkeamman tulotason maissa eläkeläiset kokevat toimeentulonsa heikommaksi kuin matalamman tulotason maissa. Ero voi liittyä esimerkiksi maiden erilaisten elintasojen luomiin kulutusta koskeviin odotuksiin. Kaikkiaan ikääntyneiden taloudellisen tyytyväisyyden voidaan todeta olevan yhteydessä sekä tuloihin että siihen, mihin omaa taloudellista asemaa kulloinkin verrataan. Näihin vertailuihin ovat keskeisesti yhteydessä sekä eläkkeelle siirtyminen että asuinmaan taloudellinen konteksti.